Kritik dan Apresiasi Terhadap Sinkretisme dalam Kekristenan IndonesiaMelalui Konsep Pneumatologi Fondasional dan Discernment Amos Yong - Christo Antusias Davarto Siahaan (Faculty of Theology Duta Wacana Christian University, 2026)
AbstractThis study explores Amos Yong’s concepts of foundational pneumatology and discernment in the context of Indonesian Christianity, particularly concerning the issue of syncretism. These two concepts provide a basis for a critical and appreciative attitude towards the adoption of local culture in Indonesian Christian practices. Foundational pneumatology and discernment emphasize the presence of the Holy Spirit in transcendent reality, which brings about positive transformation while encouraging a critical stance towards other spirits that might influence syncretistic practices. Using a literature study method, this research begins with an explanation of syncretism in relation to Indonesian Christianity, followed by an elaboration of Yong’s concepts and their application to the issue of syncretism. In conclusion, these concepts form the foundation for a critical and appreciative attitude towards local culture, enabling a constructive assessment of syncretism in the Indonesian context, with appreciation for the work of the Holy Spirit and criticism of other spirits. AbstrakStudi ini mengeksplorasi konsep pneumatologi dan discernment dari Amos Yong dalam konteks Kekristenan Indonesia, khususnya terkait isu sinkretisme. Kedua konsep ini memberikan dasar bagi sikap kritis dan apresiatif terhadap adopsi budaya lokal dalam praktik Kekristenan Indonesia. Pneumatologi fondasional dan discernment menekankan kehadiran Roh Kudus dalam realitas transenden yang membawa transformasi positif, sembari mengajak sikap kritis terhadap pengaruh roh-roh lain yang bisa mempengaruhi praktek sinkretisme. Menggunakan metode studi literatur, penelitian ini dimulai dengan penjelasan sinkretisme dalam kaitannya dengan Kekristenan Indonesia, diikuti dengan penjabaran konsep-konsep Yong, dan penerapan konsep tersebut pada isu sinkretisme. Kesimpulannya, konsep-konsep ini menjadi dasar bagi sikap kritis dan apresiatif terhadap budaya lokal, memungkinkan penilaian konstruktif terhadap sinkretisme dalam konteks Indonesia, dengan apresiasi terhadap karya Roh Kudus dan kritisisme terhadap roh-roh lain.